(untitled) (Revista Electrónica REDINE, 2023)
The roadmap is a technological tool, which in English means "road map or roadmap" and in information and communication technologies, it is known as a technological itinerary. It is a support tool at the business level that can be adapted and used in the educational field; but especially in the planning of vocational guidance activities. In this last area, it allows counselors to create activity routes to guide students about the career they want to study once they have completed their studies at the General Secondary Education level. Hence, the purpose of this essay was to analyze the use of the roadmap as a technological tool for planning in vocational guidance, through the organization of tasks to guide students in the knowledge of the career of their choice, according to their abilities and interests. Therefore, the counselor and his work team must take advantage of this innovative technological tool by integrating a virtual guide into their physical space, which helps them generate a creative interaction of their planned actions through the technological roadmap.